2012
DOI: 10.1111/j.1574-6968.2011.02479.x
|View full text |Cite
|
Sign up to set email alerts
|

A dual approach employing MALDI-TOF MS and real-time PCR for fast species identification within the Enterobacter cloacae complex

Abstract: A real-time PCR procedure targeting the gene of the molecular cochaperon DnaJ (dnaJ) was developed for specific detection of strains belonging to the Enterobacter cloacae group. The inclusivity and exclusivity of the real-time PCR assay were assessed with seven reference strains of E. cloacae, 12 other Enterobacter species and 41 non-Enterobacter strains. Inclusivity as well as exclusivity of the duplex real-time PCR was 100%. In contrast, resolution of matrix-assisted laser desorption ionization-time of fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 18 publications
1
39
0
1
Order By: Relevance
“…instead of Enterobacter kobei). Our result is in agreement with what reported by other previous studies, in which MALDI-TOF MST accurately detects Enterobacter cloacae complex although it may not discriminate some species within this complex [25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…instead of Enterobacter kobei). Our result is in agreement with what reported by other previous studies, in which MALDI-TOF MST accurately detects Enterobacter cloacae complex although it may not discriminate some species within this complex [25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…Although an obvious demarcation is shown in the dendrogram, differentiation on the basis of the reference library was not possible. Correspondingly, it has been reported for certain members of the family Enterobacteriaceae that the discriminatory power of MALDI-TOF protein profiling can be insufficient for closely related species (He et al 2010;Pavlovic et al 2012).…”
Section: Taxonomic Characterisationmentioning
confidence: 95%
“…(108,109). Finally, Pavlovic et al demonstrated that MALDI-TOF MS did not allow differentiation between different tested species of Enterobacter (110).…”
Section: Detection Of Growthmentioning
confidence: 99%